Learning curve for laparoscopic radical prostatectomy - Anna Barnaś; Tomasz Milecki; Agnieszka Ida; Michał Kasperczak; Adam Lipski; Andrzej Antczak; Wojciech A. Cieślikowski (Videosurgery and Other Miniinvasive Techniques)
Introduction: While robotic prostatectomies are gaining popularity, laparoscopic and open surgeries remain prevalent in Central and Eastern Europe due to their cost ‑effectiveness. In Poland, many urology residents report insufficient laparoscopic training. This study retrospectively evaluated the learning curve for laparoscopic radical prostatectomy (LRP). Aim: This paper aimed to assess the learning curve of a single resident performing extraperitoneal LRP. Materials and methods: We analyzed 72 patients who underwent LRP between 2016 and 2020 at a single center, divided into 5 groups (G1–G5) according to chronological order. The procedures were performed by a single urologist without on‑site supervision. Outcomes included operative duration, length of hospital stay, complications, transfusion rates, histopathology findings, biochemical recurrence, and urinary incontinence. Results: Patient characteristics were similar across all groups. The median (interquartile range [IQR]) age ranged from 61 (54–66) to 68 (66–70) years, and the median (IQR) prostate ‑specific antigen concentration, from 6.7 (5.4–8.5) to 15 (6.3–19.3) ng/ml. Higher Gleason scores were more common in the G3 and G4 groups (P = 0.05) than in the other groups. Surgery time decreased from 183 minutes in the G1 group to 130 minutes in the G5 group (P <0.001). The rates of positive surgical margins were the highest in the G3 and G4 groups (53.3% and 46.7%, respectively; P = 0.02). The rate of urinary continence improved from 66.7% in the G1 group to 86.7% in the G4 group (P = 0.36); however, without any significant difference among all groups. Biochemical recurrence rates tended to be lower in the G4 and G5 groups (6.7% and 8.3%, respectively), but the difference across all groups was nonsignificant. Grade III–V complications occurred only in the G1 group. Conclusions: Surgical outcomes improved after 15 procedures, and the oncological outcomes, after 45, with functional improvement observed later. Performing hundreds of surgeries may be required to achieve high proficiency in performing LRP